Neurogenic pulmonary edema in a 13-year-old male child, following intracranial hemorrhage due to arteriovenous malformation: a case report - Pradhan, Pratisha; Batajoo, Kabita Hada; Humagain, Sachin; Gautam, Sagar; Rana, Rohit; KC Basnet, Abhipsa (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Arteriovenous malformations (AVMs) of the brain are mostly congenital vascular lesions that can present at any age. The risk of rupture and re-rupture persists until it is completely obliterated surgically. Neurogenic pulmonary edema (NPE), a rare but life-threatening event, is characterized by an acute onset of pulmonary edema subsequent to substantial central nervous system (CNS) insult.Case presentation: We report case of 13-year-old male child who presented to our emergency room with abnormal body movement and decreased responsiveness 15 minutes prior to presentation. Past history suggested surgical intervention two years prior for right caudate hemorrhage with intraventricular extension (IVE), secondary to unknown cause, as computed tomography (CT) angiography was refused due to financial constraints. However, current imaging revealed AVM with IVE, likely a rebleed. The patient developed acute pulmonary edema, and chest radiography suggested the same. The patient was admitted and planned for decompressive craniectomy. Despite best efforts, we lost the patient on the second day of admission.Clinical discussion: NPE due to intracranial hemorrhage is rare occurrence. The clinical presentations of NPE could be as early as first hours/minutes after injury or as late as 12–24 hours after neurological injury. Although it was identified over century ago, its sporadic and relatively unpredictable nature and lack of etiologic diagnostic and treatment modalities may be responsible for its poor recognition. If misdiagnosed or misinterpreted, it can be problematic for a successful outcome.Conclusion: Prompt diagnosis and appropriate management of NPE are essential to maintain cardiopulmonary function and avoid fatal outcomes.